Firms Practice and Innovation Management: Case of Fujairah Emirate, United Arab Emirates - Ahmed, Ahmed Zain Elabdin; Sisodia, Gyanendra (International Journal of Economics and Financial Issues, 2020)
Innovation Management has received a lot of attention in the last few decades, from a vital determinant of the global competitiveness of nations over the coming decade to the primary driver of economic progress and well-being. Many countries over the world have adopted national strategic roadmaps to foster innovation and enhance its economic impact to boost productivity and growth. The United Arab Emirates (UAE) came forward with the launch of the National Innovation Strategy in 2014. Hence, this paper has investigated the strategic importance of innovation management as a need for change and firms practices in one of the UAE Emirates (Fujairah Emirate). In doing so, the paper has sought to understand whether the concept of innovation management is featured in the UAE Company’s culture and strategic plans or whether the management of the business firm is highly committed to innovation management and what an essential driver for UAE to engage in innovation management. To investigate this problem, a qualitative case study methodology is used to collect and analyze the data. Results indicate that there is a clear line of innovation management strategies in UAE and business firms in Fujairah Emirates response to concerns by integrating innovation management into business structure and systems. Keywords: Innovation Management, National Innovation Strategy, UAE, Fujairah JEL Classifications: M10, M12, M13, M14, M19, L25 DOI: https://doi.org/10.32479/ijefi.9088